(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background: Secondary neovascular glaucoma (NVG) is a refractory type of glaucoma, with its surgical treatment being a challenge. Purpose: To compare the efficacy of trabeculectomy (TE) with the formation of a filtering channel versus Ex-PRESS mini shunt surgery in surgical plus anti-VEGF treatment for NVG. Material and Methods: This study included 32 neovascular glaucoma patients (32 eyes) that received surgery due to elevated intraocular pressure (IOP > 26 mmHg) not controlled by glaucoma medication. Mean patient age was 65.2 ± 10.1 years. NVG was caused by diabetic mellitus in 22 eyes and central retinal or branch vein occlusion in 10 eyes. The TE group (23 patients) underwent our modified TE procedure (with the formation of a filtering channel), and the Ex-PRESS group (9 patients), an Ex-PRESS mini-shunt surgery. A 0.5-mg intravitreal ranibizumab injection was administered 3-5 days before surgery. Results: Study eyes had regression or resolution of iris neovascularization 3-5 days after intravitreal ranibizumab injection. In the total sample of patients, mean IOP changed from 30.9 ± 7.1 mm Hg before surgery to 17.0 ± 3.6 mm Hg at day 7 and 22.1 ± 2.9 mm Hg at 12 months. In the TE group, mean IOP changed from 31.3 ± 8.4 mm Hg before surgery to 16.7 ± 3.7 mm Hg at day 7 and 21.6 ± 2.5 mm Hg at 12 months. In the Ex-PRESS group, mean IOP changed from 30.0 ± 1.7 mm Hg before surgery to 18.0 ± 3.2 mm Hg at day 7 and 23.3 ± 2.3 mm Hg at 12 months. Mean number of anti-glaucoma medications used reduced from 2.4 ± 0.7 before surgery to 1.3 ± 0.6 at 1 month in the total sample of patients, from 2.4 ± 0.8 before surgery to 1.0 ± 0.6 at 1 month in the TE group, and from 2.6 ± 0.5 before surgery to 1.5 ± 0.7 at 1 month in the Ex-PRESS group. Conclusion: Our modification of TE (with the formation of a filtering channel) combined with preoperative 0.5-mg intravitreal ranibizumab injection is an effective treatment for NVG, and is not less effective than Ex-PRESS mini-shunt surgery with preoperative 0.5-mg intravitreal ranibizumab injection for this purpose.